FROM CAMPUS TO CLASSROOM: A NARRATIVE STUDY THE CHALLENGES AND ADAPTATION OF GENERATION Z - Regita Niken Ashari; Kevin Novantiko; Sudarmiatin; Mokhammad Nurruddin Zanky (Jurnal Penelitian Progresif, 2026)
As Generation Z enters their career preparation stage, they face an uncertain world shaped by rapid technological advancement. The teaching careers of Generation Z educators are marked by complex challenges emerging from education digitalization. This study explores the resilience and adaptive strategies of Generation Z teachers in confronting professional challenges in the digital era. Using a qualitative narrative approach, it examines their personal and professional experiences during the transition from university to the school environment. The findings indicate that many feel unprepared and uncertain about their teaching competencies. They must manage students’ digital learning behaviors while adapting to diverse school contexts and expectations. These experiences highlight the tension between digital fluency and professional maturity. The study emphasizes the necessity of institutional and systemic support to strengthen young teachers’ professionalism through structured career guidance, motivation enhancement, and digital competency development. Furthermore, creating supportive and equitable school environments is essential to nurture teacher resilience and adaptability. Ultimately, these efforts are vital to promote sustainable professional growth and ensure that Generation Z educators can thrive as competent, confident, and resilient professionals in the dynamic educational landscape of the 21st century.